POLYGYNY IN THE VIEW OF ZAINAB AL-GHAZALI: A SOCIOLOGICAL ANALYSIS OF KNOWLEDGE THROUGH THE LENS OF KARL MANNHEIM’S THEORY - Qomariyah, Siti Lailatul (Takafu: Journal of Tafsir and Gender Perspective, 2025)
Building on the arguments put forward by Riffat Hasan and Amina Wadud, which suggested that gender-biased interpretations of the Qur'an are largely the result of male exegetes, one might assume that female interpreters would naturally produce interpretations more favorable to women. However, in reality, Zainab al-Ghazali's interpretation appeared to align more closely with male-centric views. This leads to the argument that an individual's prior knowledge and social context significantly influence their understanding of the Qur'an. This study seeks to examine Zainab al-Ghazali’s perspective on polygyny as presented in her exegesis Nazarat fi Kitab Allah. This study was a library research based on Nazarat fi Kitab Allah as the primary source, employing Karl Mannheim’s sociology of knowledge—specifically, the three kinds of meaning—to analyze Zainab al-Ghazali’s interpretation of Qur’anic verses on women's roles in the household. The analysis aims to reveal the objective, expressive, and documentary meanings within her exegesis. Applying Karl Mannheim’s theory of the three kinds of meaning, this study arrived at the following conclusions: a) Objective meaning: The interpretations of early exegetes regarding polygyny tend to follow a textual-literal approach; b) Expressive meaning: Zainab al-Ghazali did not oppose the practice of polygyny, provided the husband is capable of maintaining justice. Her interpretation was influenced by the socio-political context of Egypt at the time, her affiliation with Islamic movements, and the prominent figures who shaped her thought; c) Documentary meaning: Her interpretation aligned with a quasi-objectivist traditionalist framework, reflecting a textual orientation within classical exegesis.